Preparation and characterization of chitosan derived from slipper lobster (Thenus orientalis) - RAHMAN KARNILA; BUSTARI HASAN; DIAN IRIANI; HARIFA SYAH PUTRA; MUHAMMAD FAUZI; ZULFARINA ZULFARINA (Society for Indonesian Biodiversity, 2024)
Abstract. Karnila R, Hasan B, Iriani D, Putra HS, Fauzi M, Zulfarina. 2024. Preparation and characterization of chitosan derived from slipper lobster (Thenus orientalis). Biodiversitas 25: 4360-4369. Slipper lobster (Thenus orientalis (Lund, 1793)) is a marine fishery commodity that can be utilized its large carapace (proportion >50%) to be converted into chitosan, but ideal, accurate and rapid characterization has not been developed in detecting chitosan and its derivatives as potential raw materials for nutraceuticals. In this study, the proportion and chemical composition of fan shrimp were analyzed, and the carapace of fan shrimp was determined for the degree of deacetylation of chitin and chitosan, then chitosan was evaluated for glycosidic chains using LCMS-MS from ESI sources. The method used was descriptive with 3 repetitions. The results showed that the largest proportion of the fan shrimp body was found in the carapace at 52.98%. The highest mineral content in the carapace is calcium at 752 mg/L and the lowest is phosphorus at 0.36 mg/L and higher than meat. The yield value of chitosan was 31.19% with a deacetylation degree of 80.15%. The glycosidic chain of chitosan has many amine groups from the structure of the compound 2-Amino-2-Deoxy-D-Glucose Chitosamine and 2-(Aminomethyl)-N-(3-isopropyl octahydro [1,2,4] triazolo [4,3-a] pyridine-6-il)-1 piperidinekar kotakamida which have high quality chitosan affinity, but there is a compound 5-Aminomethyl-2,4-Dihydro [1,2,4] Triazol-3-One Hydrochloride and N-[3-Methyl-2-(4-methyl-1-piperazinyl)-butyl] isoleucinamide hydrochloride which tends to be dissociated and cationized by HCl. Overall, these data suggest the glycosidic chain of slipper lobster has potential as a raw material for nutraceuticals and functional food ingredients.